Cost-Effectiveness of Cervical Cancer Screening in Women Living With HIV in South Africa: A Mathematical Modeling Study. (1st October 2018) - Campos, Nicole G.; Lince-Deroche, Naomi; Chibwesha, Carla J.; Firnhaber, Cynthia; Smith, Jennifer S.; Michelow, Pam; Meyer-Rath, Gesine; Jamieson, Lise; Jordaan, Suzette; Sharma, Monisha; Regan, Catherine; Sy, Stephen; et al.
Abstract : Background: Women with HIV face an increased risk of human papillomavirus (HPV) acquisition and persistence, cervical intraepithelial neoplasia, and invasive cervical cancer. Our objective was to determine the cost-effectiveness of different cervical cancer screening strategies among women with HIV in South Africa. Methods: We modified a mathematical model of HPV infection and cervical disease to reflect coinfection with HIV. The model was calibrated to epidemiologic data from HIV-infected women in South Africa. Clinical and economic data were drawn from in-country data sources. The model was used to project reductions in the lifetime risk of cervical cancer and incremental cost-effectiveness ratios (ICERs) of Pap and HPV DNA screening and management algorithms beginning at HIV diagnosis, at 1-, 2-, or 3-year intervals. Strategies with an ICER below South Africa's 2016 per capita gross domestic product (US5270) were considered "cost-effective." Results: HPV testing followed by treatment (test-and-treat) at 2-year intervals was the most effective strategy that was also cost-effective, reducing lifetime cancer risk by 56.6% with an ICER of US3010 per year of life saved. Other cost-effective strategies included Pap (referral threshold: HSIL+) at 1-, 2-, and 3-year intervals, and HPV test-and-treat at 3-year intervals. Pap (ASCUS+), HPV testing with 16/18 genotyping, and HPV testing with Pap or visual triage of HPV-positive women were less effective and more costly than alternatives. Conclusions: Considering per capita gross domestic product as the benchmark for cost-effectiveness, HPV test-and-treat is optimal in South Africa. At lower cost-effectiveness benchmarks, Pap (HSIL+) would be optimal. Abstract : Supplemental Digital Content is Available in the Text.